ANALISIS KINERJA KEUANGAN UNTUK MENILAI KESEHATAN PERBANKAN (Studi Pada Bank Syariah Indonesia KCP Sumbawa Diponegoro) - Novi Kadewi Sumbawati; Ulva Asri Oktavia; U Usman (Fakultas Ekonomi dan Manajemen, 2022)
This research was conducted with the aim of measuring the financial performance of Bank Syariah Indonesia KCP Sumbawa Diponegoro in 2019-2021. This research is a descriptive research that aims to describe or describe existing phenomena related to the object of research. The type of data used is quantitative data in the form of annual reports of documents and archives contained in Bank Syariah Indonesia KCP Sumbawa Diponegoro. Data analysis was performed using financial ratio analysis techniques, including liquidity ratios, solvency ratios, and profitability ratios. The results of this study indicate that the liquidity ratio, the financial performance of Bank Syariah Indonesia KCP Sumbawa Diponegoro in 2019-2021 is in a very healthy category seen from the cash ratio aspect and in the unhealthy category seen from the loan to deposit ratio aspect. The solvency ratio, the financial performance of Bank Syariah Indonesia KCP Sumbawa Diponegoro in 2019-2021 is in a very healthy category seen from the aspect of capital adequacy ratio. And the profitability ratio, the financial performance of Bank Syariah Indonesia KCP Sumbawa Diponegoro in 2019-2021 is in the unhealthy category seen from the aspect of return on equity and in the very healthy category seen from the aspect of return on assets. Based on these results, the bank must be able to improve its marketing by maximizing various media, both offline and online to support promotional activities in order to attract the attention and interest of the public so that the bank can optimally collect funds from the public.